1995
DOI: 10.1021/cm00055a019
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ferroelectric and Electroclinic Organosiloxane Liquid Crystals

Abstract: A new series of organosiloxane ferroelectric liquid crystalline materials have been synthesized, and their mesomorphic and physical properties have been characterized. The new series contains a siloxy chain attached to the hydrocarbon chain at the nonchiral end of the molecule. All materials show a very low melting point ('5 "C) and exhibit chiral smectic A (SmA) and chiral smectic C (SmC*) mesophases. The changes in the siloxy chain length strongly affect the mesomorphic behavior and electrooptic properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
46
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 1 publication
0
46
2
Order By: Relevance
“…Upon further increasing the electric field, the response time decreases. This behavior contrasts with that for a conventional SmA ‫ء‬ phase, where the response time is independent of E in the small approximation and has a small dependence on electric field for larger , 3,19 as observed in KN125. 4,20 For higher temperatures within SmA ‫ء‬ phase in TSiKN65, it was found that the response time increases to a certain value of the electric field, 3,4 but the reasons were not given nor was it highlighted as an anomalous property of the material.…”
contrasting
confidence: 56%
See 2 more Smart Citations
“…Upon further increasing the electric field, the response time decreases. This behavior contrasts with that for a conventional SmA ‫ء‬ phase, where the response time is independent of E in the small approximation and has a small dependence on electric field for larger , 3,19 as observed in KN125. 4,20 For higher temperatures within SmA ‫ء‬ phase in TSiKN65, it was found that the response time increases to a certain value of the electric field, 3,4 but the reasons were not given nor was it highlighted as an anomalous property of the material.…”
contrasting
confidence: 56%
“…This behavior contrasts with that for a conventional SmA ‫ء‬ phase, where the response time is independent of E in the small approximation and has a small dependence on electric field for larger , 3,19 as observed in KN125. 4,20 For higher temperatures within SmA ‫ء‬ phase in TSiKN65, it was found that the response time increases to a certain value of the electric field, 3,4 but the reasons were not given nor was it highlighted as an anomalous property of the material. The observed unusual behavior of the field dependent response time can well be explained by the de Vries scenario upon assuming that the reorientation of the molecular dipoles with the electric field is of the Langevin type and by considering an increase in the effective dipole moment ͑ eff ͒ with increasing field as discussed below.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…This molecular arrangement confers to the materials some of the robust mechanical properties of polymers but retains the fast electro-optic response of the low molar mass liquid crystal moiety. Due to their potential applications, low molar mass organosiloxane liquid crystals are presently the object of intense investigations [4][5][6][7]. However, it has been shown that binary mixtures of an achiral swallow-tailed compound [8] with antiferro-electric liquid crystal (S)-MHPOBC display V-shaped switching of its electro-optical response in antiferroelectric liquid crystal mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…This LC was prepared by the esterification of the cinamic acid derivative 1 and phenolic derivative 2 in the presence of 1-(3-(dimethylamino)propyl)-3-ethylcarbidimide methiodine (EDC.CH 3 I) and (dimethylamino)pyridine (DMAP) [6] as shown below:…”
mentioning
confidence: 99%